Strategic Planning For Ensuring The Stability Of Commercial Banks' Resource Base: Perencanaan Strategis untuk Menjamin Stabilitas Dasar Sumber Daya Bank Komersial - Rakhmanov Ilkhom Khurramovich (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The stability of commercial banks’ resource bases is a cornerstone of financial system resilience, particularly amid global crises and rapid digitalization that accelerate deposit withdrawals. Specific background: In Uzbekistan, recent reforms, including the 2022–2026 Development Strategy, emphasize strengthening banks through stress-testing and macroprudential buffers. Knowledge gap: Existing models such as Altman Z-Score, Ohlson, CAMELS, and Kromonov provide partial insights but lack a unified, context-specific system to measure and strategically manage resource base sustainability. Aims: This study seeks to design and apply an indicative model that integrates deposit stability, liability stability, capital adequacy, loan potential, and investment potential into a composite index. Results: Application of the model to Uzbekistan’s commercial banks (2020–2024) produced an average stability index of 59.6%, with capital indicators exerting the strongest positive effect, while overall stability remained moderate. Novelty: The model employs geometric mean integration to balance multi-dimensional indicators, ensuring adaptability, comparability, and efficiency in data collection. Implications: The framework offers banks and regulators a practical tool for monitoring resource base resilience, aligning strategic planning with liquidity and profitability goals, and guiding targeted responses through stability-based strategy selection, thereby fostering long-term competitiveness in the banking sector.Highlight : Emphasizes the importance of commercial banks’ resource base stability. The indicator model includes deposit, liability, capital, loan, and investment stability. Strategic planning focuses on resilience, liquidity, and profitability of banks. Keywords : Deposit, Deposit Stability, Liability Stability, Capital Stability, Loan Potential